2021
DOI: 10.1039/d1qm00993a
|View full text |Cite
|
Sign up to set email alerts
|

Zn-alloyed MAPbBr3 crystals with improved thermoelectric and photocatalytic properties

Abstract: Zn–MAPbBr3 crystals exhibited an improved absorption capacity and better photocatalytic degradation performance toward RhB dye and higher electrical conductivity and a more positive Seebeck coefficient, compared with a pristine MAPbBr3 sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Organic–inorganic hybrid perovskites with outstanding light absorption capability and excellent photoelectronic properties have demonstrated good performance in solar cells, light-emitting diodes, , photocatalysis, and so forth. As a promising candidate, methylammonium lead iodide perovskite (MAPbI 3 ) was first utilized as a photocatalyst for producing H 2 through solar-driven HI splitting by Park et al in 2016, which promotes the research on photocatalytic H 2 generation with halide perovskite-based materials. However, alleviating charge recombination within MAPbI 3 still remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid perovskites with outstanding light absorption capability and excellent photoelectronic properties have demonstrated good performance in solar cells, light-emitting diodes, , photocatalysis, and so forth. As a promising candidate, methylammonium lead iodide perovskite (MAPbI 3 ) was first utilized as a photocatalyst for producing H 2 through solar-driven HI splitting by Park et al in 2016, which promotes the research on photocatalytic H 2 generation with halide perovskite-based materials. However, alleviating charge recombination within MAPbI 3 still remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%
“…These peaks are associated with two distinct components of vacancy-assisted ionic diffusion in perovskite crystals, originated from Br – and MA + ions . In our previous studies and studies by other authors on MAPbBr 3 SC, it was observed that resistance and capacitance values corresponding to the mid-frequency range (1–100 Hz) exhibit an activation energy of 0.28 eV, which can be attributed to the presence of Br – ions. , However, further experimental evidence is required to fully elucidate the specific associations of ions within the probed frequency range and their influence on the interface charge accumulation and reactivity. The present measurements are focused on the change in the resistance states and the associated charge behavior.…”
Section: Resultsmentioning
confidence: 88%
“…All of the samples show three distinct XRD peaks, which correspond to the diffraction of (300), (200), and (100) lattice planes of the cubic MAPbBr 3 perovskite. 38,39 The crystal structure of the perovskite remains unchanged after doping. The XPS patterns were further obtained to confirm the effectiveness of doping.…”
Section: Resultsmentioning
confidence: 99%